2010
DOI: 10.1186/1742-9994-7-8
|View full text |Cite
|
Sign up to set email alerts
|

Visual acuity in larval zebrafish: behavior and histology

Abstract: BackgroundVisual acuity, the ability of the visual system to distinguish two separate objects at a given angular distance, is influenced by the optical and neuronal properties of the visual system. Although many factors may contribute, the ultimate limit is photoreceptor spacing. In general, at least one unstimulated photoreceptor flanked by two stimulated ones is needed to perceive two objects as separate. This critical interval is also referred to as the Nyquist frequency and is according to the Shannon samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
94
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 31 publications
8
94
0
Order By: Relevance
“…We found that the adult zebrafish acuity is about 70% of what would be predicted given their photoreceptor spacing. 23 Contrast that with optimal human performance ~20/12, which is about 80% of the predicted 20/10, and OKR technique for measuring visual capability in adult zebrafish is impressive 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…We found that the adult zebrafish acuity is about 70% of what would be predicted given their photoreceptor spacing. 23 Contrast that with optimal human performance ~20/12, which is about 80% of the predicted 20/10, and OKR technique for measuring visual capability in adult zebrafish is impressive 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Rinner et al (2005) found a band-pass CSF that peaked at 0.07-0.08 cpd, with visual acuity of 0.2-0.4 cpd. Haug et al (2010) found visual acuity of 0.16 cpd. Also using fish optokinetic nystagmus, Mueller and Neuhauss (2010) studied eye velocity as a function of stimulus contrast and spatial frequency in adult zebrafish and medaka.…”
Section: Luminance Spatial Contrast Sensitivity Of Bony Fishmentioning
confidence: 99%
“…The visual response of fish to contrast as a function of spatial frequency has been investigated in several species, some of which are laboratory animals that have been studied for numerous reasons: bluegill sunfish (Lepomis macrochirus), zebrafish (Danio rerio), medaka or Japanese killifish (Oryzias latipes), and goldfish (Carassius auratus; Bilotta & Powers, 1991;Haug, Biehlmaier, Mueller, & Neuhauss, 2010;Northmore & Dvorak, 1979;Northmore, Oh, & Celenza, 2007;Rinner, Rick, & Neuhauss, 2005; Figure 2D). Northmore and Dvorak (1979) and Bilotta and Powers (1991) used Pavlovian conditioning to suppress respiration upon the presentation of a sinusoidal grating.…”
Section: Luminance Spatial Contrast Sensitivity Of Bony Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the visual system of fish has evolved in response to a range of social and environmental pressures (Dobberfuhl et al, 2005), the visual capabilities of different species are highly variable (Lythgoe, 1979;Endler, 1990Endler, , 1993, and can be described using a range of measures including (but not limited to) acuity, temporal resolution and absolute visual sensitivity. Visual acuity, or spatial resolution, is a measure of the minimum separable angle that can be resolved by the eye (Neave, 1984) and is one of the most common measures to assess the visual capability of an animal (Reymond, 1985;Harman et al, 1986;Collin and Pettigrew, 1989;Aho, 1997;Haug et al, 2010). Knowledge of visual acuity of an animal allows us to evaluate the level of detail an animal can see in a visual scene, which is important if we wish to understand various aspects of their visual behaviour independently of the human visually guided behaviour perception.…”
Section: Introductionmentioning
confidence: 99%